Liquid biopsy for esophageal cancer: Is detection of circulating cell‐free DNA as a biomarker feasible?. Issue 1 (2nd December 2020) - Yuan, Zuyang; Wang, Xinfeng; Geng, Xiao; Li, Yin; Mu, Juwei; Tan, Fengwei; Xue, Qi; Gao, Shugeng; He, Jie
Abstract: Esophageal cancer (EC) is a common cancer and is histopathologically classified into esophageal squamous cell carcinoma and esophageal adenocarcinoma. EC is a worldwide public health issue because of late diagnosis and lack of effective therapy. In contrast to standard tumor biopsies, liquid biopsies are emerging as a tool which is minimally invasive that can complement or even substitute more classical approaches. Specifically, cell‐free DNA (cfDNA) has shown promise in cancer‐related clinical applications. Indeed, cfDNA has been shown to be an effective circulating biomarker for non‐invasive cancer diagnosis and monitoring of cancer patients. Although the clinical application of cfDNA has been reported on other cancers, few studies have evaluated its use in EC. Here, we review this relevant literature and discuss limitations and advantages of its application in the diagnosis and monitoring of EC. Abstract :